MOUSE software package: challenges and experience of fitting uncertainty management into long-term safety assessment puzzle - Valentina Svitelman; Elena Saveleva; Anton Lebedev; Gleb Kiselev; Anton Nuzhny; Alina Rukavichnikova; Evgeny Kolodin (Nuclear Engineering and Technology, 2025)
Deep geological repositories for high-level radioactive waste require comprehensive long-term safety assessments involving numerical simulations of safety-relevant processes. Managing uncertainty across all parts of such a simulation framework is challenging, as general-purpose uncertainty management toolboxes typically lack either the variety of methods or the integration capabilities to simultaneously accommodate all components of the long-term safety assessment framework. Under these circumstances, developing bespoke uncertainty-management software based on up-to-date methods and well-maintained libraries but tailored specifically for the task at hand becomes more efficient than creating various plugins and converters for general-purpose tools. This paper discusses the experience of developing the MOUSE software package to illustrate this path from a model-independent software to the uncertainty-management instrument tailored for the purposes of the numerical safety assessment framework.